PENGARUH PENGETAHUAN ANGGOTA TENTANG KOPERASI DAN KUALITAS PELAYANAN TERHADAP PARTISIPASI ANGGOTA PADA KOPERASI SRI MERSING SMK N 1 TEBING TINGGI KABUPATEN KEPULAUAN MERANTI - Riansani, Novita; Indrawati, Henny; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstak: This study aims to investigate the influence of the cooperative members' knowledge and quality of service to the participation of members of the Cooperative Sri Mersing SMK N 1 High Cliff Meranti Islands District. The population in this study were all members of the Cooperative Sri Mersing SMK N 1 High Cliff totaling 71 members. Sampling using the full sample totaled 64 minus 7 board members. Methods of data collection: questionnaire, test and documentation. Methods of data analysis in this study consisted of quantitative descriptive method, multiple linear regression analysis and hypothesis testing. The results showed that the knowledge of members and the quality of service simultaneously significantly to the participation of members of the cooperative. Analysis of the factors examined in the study showed that the variables are the dominant influence on the participation of members of the Cooperative Sri Mersing SMK N 1 High Cliff Meranti Islands District is the knowledge variable members.Keywords: participation of members, members' knowledge and quality of service